(untitled) (Commonwealth Journal of Local Governance, 2024)
Over the last few decades, governance systems across the world have prioritised citizen participation. Direct participation of the citizenry facilitates social accountability, which contributes to the advancement of good governance. In Bangladesh, following the success of donor-funded pathfinder projects, various social accountability mechanisms were legally mandated at the local level. This study examines the prescribed functioning of these mechanisms and compares this to actual practice. The study followed an explanatory, descriptive method for content analysis by reviewing relevant secondary literature. Key findings were: no practical guidelines exist in Bangladesh for managing social accountability mechanisms; citizens have limited access to information; local functionaries have insufficient understanding of their role; and social accountability has not been institutionalised. To ensure successful social accountability, it will be necessary to provide adequate guidelines, take financial and management factors into account, and make people aware of their rights. Government and NGO intervention on the demand side (local people) will be required to make this happen.